Can Faith and Hospice Coexist: Is the African American Church the Key to Increased Hospice Utilization for African Americans?. (January 2017) - Townsend, Apollo; March, Alice L.; Kimball, Jan
African Americans are twice as likely as Caucasian Americans to choose aggressive hospital treatment when death is imminent. Repeat hospitalizations are traumatic for patients and drain patient and health system resources. Hospice care is a specialized alternative that vastly improves patient quality of life at end-of-life. This study was conducted to determine if hospices partnering with African American churches to disseminate hospice education materials could increase utilization of hospice services by African Americans. Members of two African American churches ( N = 34) participated in focus group discussions to elicit beliefs about hospice care. Focus group transcripts were coded and comments were grouped according to theme. Six themes were identified. Lack of knowledge about hospice services and spiritual beliefs emerged as the top two contributing factors for underutilization of hospice services. Study findings support partnerships between hospices and African American churches to provide hospice education to the African American community.